Titanium alloy welding material for welding and filling large-thickness component as well as preparation method and application of titanium alloy welding material

By using special titanium alloy welding materials in welding large thickness TC4 titanium alloy components, the problem of roughening and poor spreading during the welding process is solved, and the weld is refined and efficiently filled, reducing defects and splashes. Improves welding efficiency and forming quality.

CN119489295APending Publication Date: 2025-02-21HARBIN WELL WELDING CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202311015989.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-14
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

During the welding process of large-thickness TC4 titanium alloy components, the existing titanium alloy wires have roughened and poorly spread the structure during the multi-pass welding process of narrow gap deep bevels, resulting in defects such as cracks on the edges of the side walls.

Method used

Provide a titanium alloy welding material for welding filling of large-thick components, including deposited metal and flux-core welding wire. The flux-core welding wire is made of TA0 titanium tape, and the flux-core components are vanadium powder, aluminum powder, PTFE powder, sodium fluoride, Sodium fluoroaluminate, potassium tartrate, magnesium chloride and potassium chloride adjust the element content and particle size of the welding wire through a specific preparation process to improve the structural refinement and wetting of the weld.

Benefits of technology

By adjusting the elements and content of welding wire alloys, the comprehensive performance of the welds is improved, and defects such as welding pores and unfusion are reduced, and high melting efficiency and good weld formation are obtained, avoiding the problem of cracks on the edges.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119489295A_ABST
    Figure CN119489295A_ABST
Patent Text Reader

Abstract

The invention discloses a titanium alloy welding material for welding and filling of a large-thickness component and a preparation method and application of the titanium alloy welding material, and belongs to the technical field of welding materials and preparation of the welding materials. The alloy elements and the content of the welding wire are reasonably adjusted, the sodium fluoride and the sodium fluoroaluminate are added into the metal powder to improve the surface tension of liquid molten drops and reduce the air hole forming tendency, meanwhile, the PTFE powder is added to improve the surface tension of the liquid molten drops, the deoxidizing and dehydrogenating effects are achieved, and the formability and the performance of a welding bead are improved; and the potassium sodium tartrate and the fluoride are combined to refine the weld structure, so that the problem that the edge is easy to crack and the like due to poor infiltration of the TC4 welding wire in the narrow-gap weld filling process is solved, and the large-thickness narrow-groove weld has better comprehensive performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a titanium alloy welding material for welding and filling of thick components, a preparation method and application thereof, and belongs to the technical field of welding materials and preparation thereof. Background Art

[0002] Ti-6Al-4V (TC4) is a medium-strength α-β titanium alloy developed in the early 1960s. It has excellent comprehensive properties and is known as a universal alloy. TC4 titanium alloy is the earliest and most widely used general titanium alloy for aviation and aerospace structures, including plates, bars and forgings, etc., with good welding and machining properties. TC4 titanium alloy is widely used in marine exploration, pressure vessels, submersibles, aerospace ships and weapons and equipment due to its many advantages such as high specific strength, wide operating temperature range, and good processing and forming. Some ships have also begun to use titanium alloy materials to manufacture transport ships, which greatly reduces their weight, operating costs and comprehensive fuel consumption. In recent years, the proportion of titanium alloy materials used in manufacturing in many countries has been increasing. Compared with overall stamping, welding preparation has small processing volume, short cycle, less consumables, and low cost, and welding materials are one of the important factors affecting the performance of welded joints.

[0003] At present, TIG welding, laser welding and electron beam welding are mostly used for titanium alloy welding, and most of the welding materials used are solid welding wires. In recent years, there have also been related invention patents for titanium alloy flux-cored welding wires, such as patent CN107363433B, which discloses a titanium alloy activator flux-cored welding wire with improved depth-to-width ratio, no welding pores, and beautiful weld formation. CN111745268A discloses a self-shielding flux-cored welding wire and preparation method suitable for TC4 titanium alloy welding, and the self-shielding effect is obtained by adding fluoride and carbon nanotubes, the arc is stable, the weld is well formed, and the welding efficiency is high; CN112404798A optimizes the components of the titanium alloy flux-cored welding wire, and obtains good strength and plastic toughness. Although the above flux-cored welding wire can obtain a welding joint with good comprehensive performance, CN 113245743 A uses Ti tubes for filling Al powder, Nb powder, Mo powder and B powder, and then rolls them, and vacuum annealing is used to obtain the required diameter of the welding wire, but in the actual production process, the welding process of large-thickness TC4 components is a multi-pass welding process with narrow gaps and deep grooves. Due to poor spreading, the coarsening of the structure causes defects such as cracks on the side wall edge. Therefore, it is very necessary to provide a titanium alloy welding material for large-thickness component welding that can refine the weld structure. Summary of the invention

[0004] Aiming at the problems of existing titanium alloy welding wires having coarsening of structure in groove and poor spreading when welding thick components, the present invention provides a titanium alloy welding material for welding thick components as well as a preparation method and application thereof.

[0005] The technical solution of the present invention:

[0006] One of the purposes of the present invention is to provide a titanium alloy welding material for welding thick components. The welding material includes deposited metal and flux-cored wire. The flux-cored wire includes a weld skin and a flux core. The weld skin is made of TA0 titanium strip through winding, drawing and reducing. The flux core includes the following components by mass percentage: 18-25% vanadium powder, 28-50% aluminum powder, 0.5-5% PTFE powder, 3-15% sodium fluoride, 5-10% sodium fluoroaluminate, 1-10% potassium sodium tartrate, 1-8% magnesium chloride, 1-8% potassium chloride, and the balance is titanium powder.

[0007] It is further defined that the weld skin includes the following elemental components by mass percentage: Ti≥99%, H≤0.015%, N≤0.03%, O≤0.15%, Fe≤0.15%.

[0008] It is further defined that the TA0 titanium strip has a thickness of 0.3 mm to 0.5 mm, a width of 8 mm to 10 mm, and is in the M annealing state.

[0009] It is further defined that the mass ratio of sodium fluoride to sodium fluoroaluminate is 1.4-1.8, and the mass ratio of the total mass of sodium fluoride and sodium fluoroaluminate to potassium sodium tartrate is 1.4-5.

[0010] It is further defined that the particle size of the aluminum powder, titanium powder and vanadium powder in the core powder is 80-120 mesh, and the particle size of the remaining powders is 80-200 mesh.

[0011] It is further defined that the deposited metal includes the following elemental components in mass percentage: Al 5.5-6.75%, V 3.5%-4.5%, C≤0.03%, O≤0.11%, Fe≤0.20%, N≤0.012%, and the balance is Ti.

[0012] It is further defined that the filling rate of the flux core in the flux cored welding wire is 13-24wt%.

[0013] The second object of the present invention is to provide a method for preparing the titanium alloy welding material for welding and filling of thick components. The specific steps for preparing the flux-cored welding wire are as follows:

[0014] (1) Preparing a core powder: mixing dried vanadium powder, aluminum powder, sodium fluoride, sodium fluoroaluminate, PTFE, magnesium chloride, calcium chloride, potassium sodium tartrate and titanium powder (remainder or no addition) under an inert gas atmosphere to obtain a core powder;

[0015] (2) Preparation of flux-cored welding wire precursor: The cleaned TA0 titanium strip is rolled into a titanium tube with a circular cross section, and flux core powder is filled in the rolling process. Then, the titanium tube containing the flux core powder is rolled, and the diameter is reduced by multiple passes, and the diameter is reduced by rolling after every two passes, until a titanium tube with an outer diameter of 2.95 mm is obtained, which is the flux-cored welding wire precursor;

[0016] (3) Preparation of flux-cored welding wire: The flux-cored welding wire precursor with an outer diameter of 2.95 mm was subjected to multiple roller drawing and diameter reduction treatments until the diameter reached 1.6 mm, and finally the wire was drawn out using a polycrystalline die to determine the diameter.

[0017] It is further defined that in (1), the sodium fluoride, magnesium chloride and potassium chloride are dried at 700-900°C, cooled and placed in a sealed container for later use; potassium sodium tartrate, vanadium powder, aluminum powder and PTFE are dried at 80-100°C, cooled and placed in a sealed container for later use.

[0018] It is further defined that the cleaning process of the TA0 titanium strip in (2) is: first, the TA0 titanium strip is cleaned with a mixed supersaturated solution of NaOH and NaNO2, then rinsed with clean water, wiped with a dry cloth, and then ultrasonically cleaned with an aqueous solution of HNO3 and HF, and dried with hot air to obtain the cleaned TA0 titanium strip.

[0019] It is further defined that the mass fraction of NaOH in the mixed supersaturated solution of NaOH and NaNO2 is 10-14%, and the mass fraction of NaNO2 is 3-5%.

[0020] It is further specified that the cleaning time of the TA0 titanium strip with the mixed supersaturated solution of NaOH and NaNO2 is 1 to 3 minutes.

[0021] It is further defined that the volume fraction of HF in the aqueous solution of HNO3 and HF is 5-8%, and the volume fraction of HNO3 is 35-40%.

[0022] Furthermore, the ultrasonic cleaning frequency is 28kHz to 40kHz, and the power density is 2W / cm 2 ~3W / cm 2 , time is 1min~3min.

[0023] It is further defined that: (2) the diameter reduction is 0.04 mm to 0.15 mm in each pass, and the surface temperature of the flux-cored wire precursor during the drawing process does not exceed 80°C.

[0024] It is further defined that in (3), the diameter is reduced by 0.02 mm to 0.1 mm in each pass, and finally a 1.55 mm polycrystalline wire drawing die is used to determine the diameter.

[0025] The third object of the present invention is to provide an application of the above-mentioned titanium alloy welding material for welding and filling thick components, specifically for laser wire welding, tungsten inert gas arc welding or plasma arc welding of TC4 titanium alloy plates.

[0026] It is further defined that multi-layer and multi-pass welding is adopted, the shielding gas is 100% Ar, the gas flow rate is 20-25L / min, the welding heat source is TIG, laser or plasma arc welding, the base material is TC4 titanium alloy plate, the interlayer temperature is controlled within 100°C, and the test plate welding is completed.

[0027] Compared with the prior art, the present invention has the following beneficial effects:

[0028] (1) The present invention reasonably adjusts the alloy elements and contents of the welding wire to make the thick narrow groove weld present better comprehensive performance. At the same time, it can improve the problem that the TC4 welding wire is not well infiltrated during the narrow gap weld filling process, resulting in defects such as cracks on the edge. At the same time, PTFE is added to the flux core to generate gas, thereby avoiding problems such as poor molten pool protection during the welding process caused by the deep groove structure.

[0029] (2) The TC4 titanium alloy filled flux-cored welding wire provided by the present invention can improve the wettability of the cladding metal, reduce defects such as welding pores and unfused welds, and obtain higher cladding efficiency and better weld formation by adjusting the ratio of the flux-cored components. Adding sodium fluoride and sodium fluoroaluminate to the metal powder can improve the surface tension of the liquid molten droplets and reduce the tendency of pore formation; adding PTFE powder can improve the surface tension of the liquid molten droplets, and at the same time has the effect of deoxidation and dehydrogenation, improving the weld formability and performance; adding chloride is beneficial to improving the thermal conductivity of the arc and increasing the depth of penetration; potassium sodium tartrate and fluoride have the effect of refining the structure; the addition of fluoride reduces the probability of undercutting the edge of the weld, and reduces the risk of cracks caused by uneven edge cracks.

[0030] (3) The preparation process of the flux-cored welding wire for titanium alloy welding provided by the present invention is relatively simple, the welding penetration is large, the welding spatter is extremely small, there is no slag or micro-slag, the wetting and spreading performance are good, and the weld formation is good.

[0031] (4) The flux-cored welding wire for TC4 titanium alloy filling provided by the present invention can be applied to the fields of laser wire filling welding, tungsten inert gas arc welding or plasma arc welding. It has good welding processability, excellent comprehensive mechanical properties, high welding efficiency, and no slag or micro-slag after welding. It is suitable for the welding of TC4 titanium alloy. When welding TC4 titanium alloy, the joint performance is equivalent to that of the parent material. The alloy system of the weld component is basically consistent with that of the parent material, and no component transition and segregation will occur. The penetration depth is significantly increased, the deposition efficiency is improved, the spatter in the welding process is small, the weld formation is good, and it has good application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 This is a microstructure photograph of a weld of a TC4 titanium alloy plate welded using the titanium alloy welding material prepared in Example 3;

[0033] Figure 2 This is a photo of the weld structure of TC4 titanium alloy plate welded using the titanium alloy welding material prepared in Comparative Example 1;

[0034] Figure 3 This is a photo of the weld structure of TC4 titanium alloy plate welded using the titanium alloy welding material prepared in Comparative Example 2. DETAILED DESCRIPTION

[0035] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.

[0036] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0037] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.

[0038] The experimental methods used in the following examples are conventional methods unless otherwise specified. The materials, reagents, methods and instruments used are conventional materials, reagents, methods and instruments in the art unless otherwise specified, and can be obtained through commercial channels by those skilled in the art.

[0039] Example 1

[0040] The welding material provided in this embodiment includes cladding powder and flux-cored welding wire. The flux-cored welding wire includes welding skin and flux core. The filling rate of the flux core in the flux-cored welding wire is 17-18wt%.

[0041] The core comprises the following components by mass percentage: 27% vanadium powder, 47% aluminum powder, 4% PTFE powder, 5% sodium fluoride, 7% sodium fluoroaluminate, 5% potassium sodium tartrate, 3% magnesium chloride, and 2% potassium chloride. The particle size of the vanadium powder and aluminum powder is 80-120 meshes, and the particle size of the remaining powders is 80-200 meshes.

[0042] The weld skin includes the following elements by mass percentage: Ti ≥ 99%, H ≤ 0.015%, N ≤ 0.02%, O ≤ 0.15%, Fe ≤ 0.15%. The weld skin is made of TA0 titanium strip through rolling, drawing and reducing. The thickness of TA0 titanium strip is 0.35mm, the width is 9.8mm, and the state is M annealing state.

[0043] The deposited metal includes the following elemental compositions by mass percentage: Al 5.73%, V 3.97%, C 0.013%, O 0.1%, Fe 0.13%, N 0.01%, and the balance is Ti.

[0044] The preparation method of the flux-cored welding wire provided in this embodiment is carried out according to the following steps:

[0045] 1. Cleaning TA0 titanium strip: First, clean the TA0 titanium strip with a mixed supersaturated solution of NaOH and NaNO2. The mass fraction of NaOH in the mixed supersaturated solution of NaOH and NaNO2 is 12%, and the mass fraction of NaNO2 is 4%. The cleaning time is 2 minutes. After cleaning, rinse with clean water and wipe with a dry cloth. Then, use an aqueous solution of HNO3 and HF for ultrasonic cleaning. The volume fraction of HF in the aqueous solution of HNO3 and HF is 6%, and the volume fraction of HNO3 is 36%. The ultrasonic cleaning frequency is 29kHz, and the power density is 2.5W / cm 2 , time is 2min.

[0046] 2. Prepare flux core powder: Put vanadium powder, aluminum powder, PTFE powder, sodium fluoride, sodium fluoroaluminate, potassium sodium tartrate, magnesium chloride and potassium chloride in proportion into a three-dimensional mixing tank under argon atmosphere protection. The ball milling time is 1.5 hours, and the three-dimensional powder mixing speed is 15r / min. Use a loose density meter to measure the loose density and obtain the flux core powder. Before mixing, sodium fluoride, magnesium chloride and potassium chloride are dried at 800°C respectively, and after cooling, they are placed in sealed containers for standby use; potassium sodium tartrate, vanadium powder, aluminum powder and PTFE are dried at 90°C respectively, and after cooling, they are placed in sealed containers for standby use. Baking removes crystal water and other impurity elements to prevent them from being brought into the welding wire.

[0047] 3. Preparation of flux-cored welding wire precursor: The cleaned TA0 titanium strip is rolled into a U-shape, filled with flux core powder, and rolled into a titanium tube with a circular cross-section. The titanium tube containing the flux core powder is then rolled, and the diameter is reduced by multiple passes, and the diameter is reduced by rolling after every two passes, until a titanium tube with an outer diameter of 2.95 mm is obtained, which is the flux-cored welding wire precursor;

[0048] 4. Preparation of flux-cored welding wire: The flux-cored welding wire precursor with an outer diameter of 2.95 mm is subjected to multiple cold-drawn rolling and reducing wire drawing processes, and the diameters of the flux-cored welding wire precursors are 2.95 mm, 2.85 mm, 2.78 mm, 2.72 mm, 2.7 mm, 2.63 mm, 2.57 mm, 2.52 mm, 2.47 mm, 2.45 mm, 2.39 mm, 2.34 mm, 2.3 mm, 2.27 mm, The roller dies are 2.25mm, 2.22mm, 2.18mm, 2.14mm, 2.1mm, 1.96mm, 1.92mm, 1.86mm, 1.82mm, 1.76mm, 1.72mm, 1.68mm, and 1.65mm, and finally a 1.55mm polycrystalline drawing die is used to determine the size. The temperature of each cold drawing and reducing drawing die is ≤60℃ until a flux-cored welding wire with a diameter of 1.6mm is obtained.

[0049] Example 2

[0050] The welding material provided in this embodiment includes cladding powder and flux-cored welding wire. The flux-cored welding wire includes welding skin and flux core. The filling rate of the flux core in the flux-cored welding wire is 18-19wt%.

[0051] The core comprises the following components by mass percentage: 23% vanadium powder, 36% aluminum powder, 3% PTFE powder, 5% sodium fluoride, 9% sodium fluoroaluminate, 10% potassium sodium tartrate, 2% magnesium chloride, 2% potassium chloride, and the balance is titanium powder. The particle size of the vanadium powder, aluminum powder and titanium powder is 80-120 mesh, and the particle size of the remaining powders is 80-200 mesh.

[0052] The weld skin includes the following elements by mass percentage: Ti ≥ 99%, H ≤ 0.015%, N ≤ 0.02%, O ≤ 0.15%, Fe ≤ 0.15%. The weld skin is made of TA0 titanium strip through rolling, drawing and reducing. The thickness of TA0 titanium strip is 0.4mm, the width is 9.8mm, and the state is M annealing state.

[0053] The deposited metal includes the following elemental compositions by mass percentage: Al 6.44%, V 4.1%, C 0.013%, O 0.099%, Fe≤0.20%, N 0.008%, and the balance is Ti.

[0054] The preparation method of the flux-cored welding wire provided in this embodiment is carried out according to the following steps:

[0055] 1. Cleaning TA0 titanium strip: First, clean the TA0 titanium strip with a mixed supersaturated solution of NaOH and NaNO2. The mass fraction of NaOH in the mixed supersaturated solution of NaOH and NaNO2 is 13%, and the mass fraction of NaNO2 is 5%. The cleaning time is 2 minutes. After cleaning, rinse with clean water and wipe with a dry cloth. Then, use an aqueous solution of HNO3 and HF for ultrasonic cleaning. The volume fraction of HF in the aqueous solution of HNO3 and HF is 8%, and the volume fraction of HNO3 is 38%. The ultrasonic cleaning frequency is 35kHz, and the power density is 2.5W / cm 2 , time is 2min.

[0056] 2. Prepare flux core powder: Put vanadium powder, aluminum powder, titanium powder, PTFE powder, sodium fluoride, sodium fluoroaluminate, potassium sodium tartrate, magnesium chloride and potassium chloride in proportion into a three-dimensional mixing tank under argon atmosphere protection. The ball milling time is 1.5 hours, and the three-dimensional powder mixing speed is 15r / min. Use a loose density meter to measure the loose density and obtain the flux core powder. Before mixing, sodium fluoride, magnesium chloride and potassium chloride are dried at 800°C respectively, and after cooling, they are placed in sealed containers for standby use; potassium sodium tartrate, vanadium powder, aluminum powder and PTFE are dried at 90°C respectively, and after cooling, they are placed in sealed containers for standby use. Baking removes crystal water and other impurity elements to prevent them from being brought into the welding wire.

[0057] 3. Preparation of flux-cored welding wire precursor: The cleaned TA0 titanium strip is rolled into a U-shape, filled with flux core powder, and rolled into a titanium tube with a circular cross-section. The titanium tube containing the flux core powder is then rolled, and the diameter is reduced by multiple passes, and the diameter is reduced by rolling after every two passes, until a titanium tube with an outer diameter of 2.95 mm is obtained, which is the flux-cored welding wire precursor;

[0058] 4. Preparation of flux-cored welding wire: The flux-cored welding wire precursor with an outer diameter of 2.95mm is subjected to multiple cold-drawn rolling and reducing wire drawing processes, and the diameters of the flux-cored welding wires are 2.95mm, 2.9mm, 2.85mm, 2.8mm, 2.7mm, 2.6mm, 2.5mm, 2.45mm, 2.39mm, 2.34mm, 2.3mm, 2.27mm, 2.25mm, 2.22mm, 2.18mm, 2.14mm, 2.1m in turn. m, 1.96mm, 1.92mm, 1.86mm, 1.82mm, 1.76mm, 1.72mm, 1.68mm, and 1.65mm roller dies are used, and finally a 1.55mm polycrystalline drawing die is used for sizing. The drawing die in the diameter reduction process adopts a combined cooling of liquid cooling and air cooling to make the temperature of each cold drawing and diameter reduction drawing die 60°C to ensure that the surface temperature of the flux-cored welding wire precursor during the drawing process does not exceed 80°C, until a flux-cored welding wire with a diameter of 1.6mm is obtained.

[0059] Example 3

[0060] The welding material provided in the embodiment includes cladding powder and flux-cored welding wire. The flux-cored welding wire includes welding skin and flux core. The filling rate of the flux core in the flux-cored welding wire is 20-21wt%.

[0061] The core comprises the following components by mass percentage: 21% vanadium powder, 34% aluminum powder, 5% PTFE powder, 15% sodium fluoride, 10% sodium fluoroaluminate, 5% potassium sodium tartrate, 7% magnesium chloride, 7% potassium chloride, and the balance is titanium powder. The particle size of the vanadium powder, aluminum powder and titanium powder is 80-120 mesh, and the particle size of the remaining powders is 80-200 mesh.

[0062] The weld skin includes the following elements by mass percentage: Ti ≥ 99%, H ≤ 0.015%, N ≤ 0.02%, O ≤ 0.15%, Fe ≤ 0.15%. The weld skin is made of TA0 titanium strip through rolling, drawing and reducing. The thickness of TA0 titanium strip is 0.3mm, the width is 8mm, and the state is M annealing state.

[0063] The deposited metal includes the following elemental compositions by mass percentage: Al 6.7%, V 4.3%, C 0.021%, O 0.07%, Fe 0.18%, N 0.008%, and the balance is Ti.

[0064] The preparation method of the flux-cored welding wire provided in this embodiment is carried out according to the following steps:

[0065] 1. Cleaning TA0 titanium strip: First, clean the TA0 titanium strip with a mixed supersaturated solution of NaOH and NaNO2. The mass fraction of NaOH in the mixed supersaturated solution of NaOH and NaNO2 is 13%, and the mass fraction of NaNO2 is 5%. The cleaning time is 2 minutes. After cleaning, rinse with clean water and wipe with a dry cloth. Then, use an aqueous solution of HNO3 and HF for ultrasonic cleaning. The volume fraction of HF in the aqueous solution of HNO3 and HF is 5%, and the volume fraction of HNO3 is 40%. The ultrasonic cleaning frequency is 40kHz, and the power density is 3.0W / cm 2 , time is 2min.

[0066] 2. Prepare flux core powder: Put vanadium powder, aluminum powder, titanium powder, PTFE powder, sodium fluoride, sodium fluoroaluminate, potassium sodium tartrate, magnesium chloride and potassium chloride into a ball mill under argon atmosphere according to the proportion. The ball milling time is 1.0h and the ball milling speed is 15r / min. Use a loose density meter to measure the loose density and obtain the flux core powder. Before mixing, sodium fluoride, magnesium chloride and potassium chloride are dried at 800℃ respectively, and then placed in a sealed container after cooling for later use; potassium sodium tartrate, vanadium powder, aluminum powder and PTFE are dried at 90℃ respectively, and then placed in a sealed container after cooling for later use. Baking removes crystal water and other impurity elements to prevent them from being brought into the welding wire.

[0067] 3. Preparation of flux-cored welding wire precursor: The cleaned TA0 titanium strip is rolled into a U-shape, filled with flux core powder, and rolled into a titanium tube with a circular cross-section. The titanium tube containing the flux core powder is then rolled, and the diameter is reduced by multiple passes, and the diameter is reduced by rolling after every two passes, until a titanium tube with an outer diameter of 2.95 mm is obtained, which is the flux-cored welding wire precursor;

[0068] 4. Preparation of flux-cored welding wire: The flux-cored welding wire precursor with an outer diameter of 2.95mm is subjected to multiple cold-drawn rolling and reducing wire drawing processes, and the diameters of the flux-cored welding wires are 2.95mm, 2.9mm, 2.85mm, 2.8mm, 2.75mm, 2.70mm, 2.65mm, 2.60mm, 2.55mm, 2.50mm, 2.45mm, 2.40mm, 2.35mm, 2.30mm, 2.25mm, 2.20mm, 2.15mm, 2. The wire drawing dies of diameters of 1.5mm, 2.1mm, 2.05mm, 2.0mm, 1.95mm, 1.9mm, 1.85mm, 1.8mm, 1.75mm, 1.7mm, 1.65mm, 1.6mm and 1.55mm are used. The wire drawing dies in the diameter reduction process adopt a combined cooling of liquid cooling and air cooling to make the temperature of each cold drawing and diameter reduction drawing die 60℃, ensuring that the surface temperature of the flux-cored welding wire precursor in the drawing process does not exceed 80℃, until a flux-cored welding wire with a diameter of 1.6mm is obtained.

[0069] Comparative Example 1

[0070] The difference between this comparative example and Example 3 is that the drug core does not contain potassium sodium tartrate, and the specific drug core comprises the following components by mass percentage: 21% vanadium powder, 34% aluminum powder, 5% PTFE powder, 15% sodium fluoride, 10% sodium fluoroaluminate, 7% magnesium chloride, 7% potassium chloride, and the balance is titanium powder; the rest of the operation process and parameter settings are the same as those in Example 3.

[0071] Comparative Example 2

[0072] The difference between this comparative example and Example 3 is that the core does not contain sodium fluoride and sodium fluoroaluminate, and the specific core comprises the following components by mass percentage: 21% vanadium powder, 34% aluminum powder, 5% PTFE powder, 5% potassium sodium tartrate, 7% magnesium chloride, 7% potassium chloride, and the balance is titanium powder; the rest of the operation process and parameter settings are the same as those in Example 3.

[0073] Effect example

[0074] The titanium alloy welding materials obtained in Example 3, Comparative Example 1 and Comparative Example 2 are welded to TC4 titanium alloy plates with a specification of 400×200×20mm. Specifically, a U-shaped groove is processed on the base material TC4 titanium alloy plate, the single-side groove angle is 2°, the groove root gap is 3mm, and multi-layer and multi-pass welding is adopted. The protective gas is 100% Ar, the gas flow rate is 20-25L / min, and the welding heat source is TIG, laser or plasma arc welding. The specific welding parameters of the comparative experiment are as follows: a laser heat source is used, the power is 4KW, the wire feeding speed is 0.6m / min, the welding speed is 0.4mm / min, the defocus amount is +15mm, and the interlayer temperature is controlled within 100°C to complete the welding.

[0075] By comparing the welds, it can be seen that the welds obtained by welding with the titanium alloy welding material provided in Example 3 have beautiful shapes, and the surface slag can be removed by cleaning with a wire brush, and the performance is excellent. With reference to GB / T 25774.1-2010 "Inspection of welding materials Part 1: Preparation and inspection of mechanical properties of steel, nickel and nickel alloy deposited metal specimens", the tensile performance test of the welded test plate was carried out. The results show that the welded test plate welded with the titanium alloy welding material provided in Example 3 can meet the index requirements of GB / T30562-2014, STi6402 and STi6408.

[0076] The microstructure morphology of the weld was characterized and the results were as follows: Figure 1-3 As shown, compared Figure 1-Figure 3 It can be seen that welding materials containing potassium sodium tartrate, sodium fluoride and sodium fluoroaluminate have a certain refinement effect on the weld structure, and no cracks are found in multi-layer and multi-pass welding. However, adding only sodium fluoride and sodium fluoroaluminate, or only adding potassium sodium tartrate, cannot refine the weld structure, which proves that the combined use of potassium sodium tartrate and fluoride has the effect of refining the structure.

[0077] Although the present invention has been disclosed as above in the preferred embodiment, it is not intended to limit the present invention. Anyone familiar with this technology can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention should be based on the definition of the claims.

Claims

1. A titanium alloy welding material for welding thick components, characterized in that: The welding material comprises cladding powder and flux-cored welding wire, the flux-cored welding wire comprises welding skin and flux core, the welding skin is made of TA0 titanium strip through winding, drawing and reducing; the flux core comprises the following components by mass percentage: 18-25% of vanadium powder, 28-50% of aluminum powder, 0.5-5% of PTFE powder, 3-15% of sodium fluoride, 5-10% of sodium fluoroaluminate, 1-10% of sodium potassium tartrate, 1-8% of magnesium chloride, 1-8% of potassium chloride, and the balance is titanium powder.

2. The titanium alloy welding material for welding thick components according to claim 1, characterized in that: The weld skin includes the following element components by mass percentage: Ti≥99%, H≤0.015%, N≤0.03%, O≤0.15%, Fe≤0.15%.

3. The titanium alloy welding material for welding thick components according to claim 1 or 2, characterized in that: The thickness of TA0 titanium strip is 0.3mm~0.5mm, the width is 8mm~10mm, and the state is M annealing state.

4. The titanium alloy welding material for welding thick components according to claim 1, characterized in that: The mass ratio of sodium fluoride to sodium fluoroaluminate is 1.4-1.8, and the mass ratio of the total mass of sodium fluoride and sodium fluoroaluminate to potassium sodium tartrate is 1.4-5.

5. The titanium alloy welding material for welding thick components according to claim 1, characterized in that: The particle sizes of aluminum powder, titanium powder and vanadium powder in the core are 80-120 meshes, and the particle sizes of other powders are 80-200 meshes.

6. The titanium alloy welding material for welding thick components according to claim 1, characterized in that: The deposited metal includes the following elemental components by mass percentage: Al 5.5-6.75%, V 3.5-4.5%, C≤0.03%, O≤0.11%, Fe≤0.20%, N≤0.012%, and the balance is Ti.

7. The titanium alloy welding material for thick component welding according to claim 1, characterized in that: The filling rate of the flux core in the flux cored welding wire is 13-24wt%.

8. A method for preparing the titanium alloy welding material according to claim 1, characterized in that: The preparation method of flux-cored welding wire comprises: (1) Preparing a core powder: mixing dried vanadium powder, aluminum powder, sodium fluoride, sodium fluoroaluminate, PTFE, magnesium chloride, calcium chloride, potassium sodium tartrate and titanium powder under an inert gas atmosphere to obtain a core powder; (2) Preparation of flux-cored welding wire precursor: The cleaned TA0 titanium strip is rolled into a titanium tube with a circular cross section, and flux core powder is filled in the rolling process. Then, the titanium tube containing the flux core powder is rolled, and the diameter is reduced by rolling after multiple roller drawing, and the diameter is reduced after every two reduction passes, until a titanium tube with an outer diameter of 2.95 mm is obtained, which is the flux-cored welding wire precursor; (3) Preparation of flux-cored welding wire: The flux-cored welding wire precursor with an outer diameter of 2.95 mm was subjected to multiple roller drawing and diameter reduction treatments until the diameter reached 1.6 mm, and finally the wire was drawn out using a polycrystalline die to determine the diameter.

9. The method for preparing a flux-cored welding wire according to claim 8, characterized in that: (2) The diameter is reduced by 0.04mm to 0.15mm in each pass; (3) The diameter is reduced by 0.02mm to 0.1mm in each pass, and finally a 1.55mm polycrystalline wire drawing die is used to determine the diameter.

10. Use of the titanium alloy welding material according to any one of claims 1 to 7, characterized in that: Used for laser wire welding, argon tungsten arc welding or plasma arc welding of TC4 titanium alloy plates.

Citation Information

Patent Citations

  • A flux-cored welding wire for welding titanium and titanium alloys

    CN107363433B

  • Self-shielded flux-cored wire suitable for welding of TC4 titanium alloy

    CN111745268A

  • TC4 titanium alloy flux-cored wire and preparation method thereof

    CN112404798A